Structural insights into the role of reduced cysteine residues in SOD1 amyloid filament formation - Yeongjin Baek; Hyunmin Kim; Dukwon Lee; Doyeon Kim; Eunbyul Jo; Soung-Hun Roh; Nam-Chul Ha (Proceedings of the National Academy of Sciences, 2025)
The formation of superoxide dismutase 1 (SOD1) filaments has been implicated in amyotrophic lateral sclerosis (ALS). Although the disulfide bond formed between Cys57 and Cys146 in the active state has been well studied, the role of the reduced cysteine residues, Cys6 and Cys111, in SOD1 filament formation remains unclear. In this study, we investigated the role of reduced cysteine residues by determining and comparing cryoelectron microscopy (cryo-EM) structures of wild-type (WT) and C6A/C111A SOD1 filaments under thiol-based reducing and metal-depriving conditions, starting with protein samples possessing enzymatic activity. The C6A/C111A mutant SOD1 formed filaments more rapidly than the WT protein. The mutant structure had a unique paired-protofilament arrangement, with a smaller filament core than that of the single-protofilament structure observed in WT SOD1. Although the single-protofilament form developed more slowly, cross-seeding experiments demonstrated the predominance of single-protofilament morphology over paired protofilaments, regardless of the presence of the Cys6 and Cys111 mutations. These findings highlight the importance of the number of amino acid residues within the filament core in determining the energy requirements for assembly. Our study provides insights into ALS pathogenesis by elucidating the initiation and propagation of filament formation, which potentially leads to deleterious amyloid filaments.